Editorial Revista Espinhaço (Revista Espinhaço, 2016)
The purpose of the publications in this issue is to raise the value of such a multi-disciplinary analysis for climate change impacts and provide a scientific platform for those seeking knowledge, inspiration and professional guidance in this area. Obviously, this issue can be a good start in the journal and hence further publications in the relevant special issues would be necessary in the future. I look forward to working with experts in this multi-disciplinary environment to help us achieve a brighter future in which the most efficient adaptation and mitigation strategies of climate change can be identified and implemented.This special issue also brings a very interesting interview with Dr. Bette Otto Bliesner. Dr. Bliesner is a researcher at the National Center for Atmospheric Research (NCAR) and expert in climate modeling and historic climate change. In this interview, she brings significant reflections about her recent work as an IPCC contributor. This interview was conducted by Kourosh Behzadian (University of West London), Douglas Sathler (FIH/Cegeo/UFVJM) and Lorena Fleury (UFRGS). In addition, Lilian Yamamoto reviewed the book written by Diogo Andreola Serraglio entitled “Environmental refugees by the international law”Referências
Keywords: Editorial